Évaluations d’incidences Natura 2000 et sports de nature : un virage paradigmatique dans la conduite d’une action publique ? - Ludovic Falaix (VertigO)
This study endeavours to investigate to what extent the operational implementation of a public policy as regards the outdoors sports seems to slip from the responsibility of the Ministry of Sport, to the benefit of the Ministry of Ecology, Sustainable Development and Energy, which has seized this authority on behalf of the environmental conservation of the sports practice areas. This study is based on the analysis of the legal documentation and demonstrates the dispersion of the prerogatives asserted by the Ministry of Sports, which nonetheless defined the frame of reference of the public policy that advises to support the “proficient development” of outdoors activities. Does the reinforcement of the environmental constraints, which are implied by the decree n° 2010-365 related to the evaluation of the impact of Natura 2000, speed the Ministry of Sport up into a legitimacy crisis in so far as the analysis of the impact of the practice of outdoors activities on the natural environment, that is apprehended as a coercion means to contain the spontaneous development of outdoors sports, does not come under the responsibility of the Ministry of Sports ?